Maternal and cord plasma branched‐chain amino acids and child risk of attention‐deficit hyperactivity disorder: a prospective birth cohort study. (22nd September 2020) - Anand, Neha S.; Ji, Yuelong; Wang, Guoying; Hong, Xiumei; van der Rijn, Madeleine; Riley, Anne; Pearson, Colleen; Zuckerman, Barry; Wang, Xiaobin
Abstract : Background: Branched‐chain amino acids (BCAA: leucine, isoleucine, and valine) are essential amino acids involved in biological functions of brain development and recently linked with autism. However, their role in attention‐deficit hyperactivity disorder (ADHD) is not well‐studied. We investigated individual and combined relationships of maternal plasma and newborn cord plasma BCAAs with childhood development of ADHD. Methods: We utilized the Boston Birth Cohort, a predominantly urban, low‐income, US minority population. Child developmental outcomes were defined in three mutually exclusive groups – ADHD, neurotypical (NT), or other developmental disabilities based on physician diagnoses per ICD‐9 or 10 in medical records. The final sample included 626 children (299 ADHD, 327 NT) excluding other developmental disabilities. BCAAs were measured by liquid chromatography–tandem mass spectrometry. We used factor analysis to create composite scores of maternal and cord BCAA, which we divided into tertiles. Logistic regressions analyzed relationships between maternal or cord BCAA tertiles with child ADHD risk, controlling for maternal race, age, parity, smoking, education, low birth weight, preterm birth, and child sex. Additionally, we analyzed maternal and cord plasma BCAAs jointly on child ADHD risk. Results: Adjusted logistic regression found significantly increased odds of child ADHD diagnosis for the second (OR 1.63, 95% CI: 1.04, 2.54, p = .032) and third tertiles (OR 2.01, 95% CI: 1.28, 3.15, p = .002) of cord BCAA scores compared to the first tertile. This finding held for the third tertile when further adjusting for maternal BCAA score. There was no significant association between maternal BCAA score and child ADHD risk, nor a significant interaction between maternal and cord BCAA scores. Conclusions: In this prospective US birth cohort, higher cord BCAA levels were associated with a greater risk of developing ADHD in childhood. These results have implications for further research into mechanisms of ADHD development and possible early life screening and interventions.